Features of cadets' adaptation universities Ukrainian Interior Ministry to study the art of sambo - V.V. Serebryak; S.V. Popov (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose : to study the problem of adaptation of students to the study of throwing techniques Sambo in the educational process of professional orientation. Material : the study involved 53 first-year cadet. Also 8 teachers - experts. Results : the initial study of the features of self-defense techniques without weapons in the universities of the Interior Ministry of Ukraine. The factors that impede the development of technical action: lack of preparedness of students on basic psychophysical parameters, the desire to avoid pain when you fall; big breaks between classes. Developed a set of special exercises aimed at improving the mental and physical qualities of the future police officers. Complex promotes adaptation to the study of self-defense techniques without weapons. An efficiency of specific exercises to improve motor skills formation and neutralization of negative factors. Conclusions : recommend the use in the educational process special physical training specific exercises. Exercises gradually become more complex in structure as close as possible to the difficult coordination in unarmed combat.